DAMPAK LOKASI PEMAKAMAN UMUM SERTA EFEKTIFITAS KEWENANGAN KADES DALAM PENGATURAN LOKASI PEMAKAMAN UMUM DI DESA JERUK KABUPATEN BANGKA TENGAH PROVINSI BANGKA BELITUNG - Baharudin Baharudin (Justici, 2021)
Public burial place is an area of ​​land provided for funeral purposes for everyone regardless of religion and class, but if it is not managed properly it can have a negative impact on the development of the area, including reduced land for settlements, agriculture and low NJOP value of land. Jeruk village, Central Bangka Regency, Bangka Belitung Province where the PERDA issued by the local government cannot be implemented effectively by the village head due to unclear arrangements on the authority of the Village head to regulate the funeral location